2011
DOI: 10.1099/mic.0.047365-0
|View full text |Cite
|
Sign up to set email alerts
|

A novel antimicrobial peptide significantly enhances acid-induced killing of Shiga toxin-producing Escherichia coli O157 and non-O157 serotypes

Abstract: Shiga toxin-producing Escherichia coli (STEC) colonizes the human intestine, causing haemorrhagic colitis and haemolytic uraemic syndrome (HUS). Treatment options are limited to intravenous fluids in part because sublethal doses of some antibiotics have been shown to stimulate increased toxin release and enhance the risk of progression to HUS. Preventative antimicrobial agents, especially those that build on the natural antimicrobial action of the host defence, may provide a better option. In order to survive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
23
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 34 publications
3
23
0
Order By: Relevance
“…Because mammalian host defences such as gastric acid and the oxidative burst in macrophages induce DNA damage and thus DNA repair in bacterial invaders, use of wrwycr in antimicrobial therapy may increase the efficacy of these natural defence systems. Recently, wrwycr was shown to inhibit the growth of Salmonella enterica serovar Typhimurium inside macrophages (Su et al, 2010) and significantly enhance acid-induced killing of Shiga toxin-producing strains of Escherichia coli associated with haemolytic uraemia syndrome (Lino et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Because mammalian host defences such as gastric acid and the oxidative burst in macrophages induce DNA damage and thus DNA repair in bacterial invaders, use of wrwycr in antimicrobial therapy may increase the efficacy of these natural defence systems. Recently, wrwycr was shown to inhibit the growth of Salmonella enterica serovar Typhimurium inside macrophages (Su et al, 2010) and significantly enhance acid-induced killing of Shiga toxin-producing strains of Escherichia coli associated with haemolytic uraemia syndrome (Lino et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…We previously demonstrated that pretreatment of EHEC with wrwycr followed by acid stress similar to that of gastric acid profoundly decreases the survival of EHEC seropathotypes that are highly associated with HUS (Lino et al, 2011). Furthermore, acid-induced EHEC killing was dose dependent with peptide concentration.…”
Section: Introductionmentioning
confidence: 99%
“…These intermediate structures must be fully resolved in order for DNA repair to proceed. Failure to resolve these structures is lethal to the bacteria (Lino et al, 2011). If acid-induced DNA damage repair is ablated through inhibition of HJ resolution, this would compromise EHEC survival and thereby decrease the potential for EHEC infection of the GI tract.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations